In silico structural interactions of trichoderma harzianum T12 β-glucosidase towards the cell wall components of macrophomina phaseolina - Mohammad Hakim Mohammad Hood (Kulliyyah of Science, International Islamic University Malaysia, 2021)
An empirical study showed the Trichoderma harzianum β-glucosidase T12 (ThBglT12) was a greener alternative to chemical fungicides in inhibiting the phytopathogenic fungus M. phaseolina by digesting its cell-wall. However, the underlying molecular mechanisms of cell wall recognition by the ThBglT12 remains elusive. Therefore, this study aims to predict the binding mechanism and illustrate the molecular interactions of the ThBglT12 with the M. phaseolina mycelial cell wall components by utilising molecular docking and molecular dynamics simulation. The binding location was identified by a consensus of residues predicted by COACH tool, blind docking, and multiple sequence alignment. The study discovered that molecular recognition by ThBglT12 occurred through interactions between the α-1,3-glucan, β-1,3-glucan, β-1,3/1,4-glucan, and chitin components of M. phaseolina, with corresponding binding energies of −7.4, −7.6, −7.5 and −7.8 kcal/mol. The low binding energies seen here indicated favourable binding affinities between the tested substrates that represented the pathogenic fungal cell wall components and ThBglT12. The residue consensus verified the participation of Glu172, Tyr304, Trp345, Glu373, Glu430, and Trp431 in the active site pocket of ThBglT12 to bind the substrates, of which Trp345 was the common interacting residue. Root-mean square deviation, root-mean square fluctuation, total energy and minimum distance calculation from MD simulation further confirmed the stability and the closeness of the binding substrates into the ThBglT12 active site pocket. The hydrogen bond occupancy by Tyr304, Glu373, Glu430, and Trp431 corroborated with the role of the nucleophile for substrate recognition and specificity, crucial for cleaving the β-1,4 linkage. Further investigation showed the proximity of Glu373 to the anomeric carbon of β-1,3/1,4-glucan (3.5Å) and chitin (5.5Å) indicates the readiness of the nucleophile to form enzyme-substrate intermediate. Plus, the neighboring water molecule appeared to be correctly positioned and oriented towards the anomeric carbon to hydrolyse the β-1,3/1,4-glucan and chitin, less than 4.0Å away from the substrates’ anomeric carbon. Both molecular docking and MD studies indicated that there are interactions between ThBglT12 and fungal cell wall components, however there are slight difference or preference of the enzyme for these component. In a nutshell, the study verified that the ThBglT12 is a good alternative fungicide to inhibit the growth of M. phaseolina.